Zoledronic Acid-Loaded Hybrid Hyaluronic Acid/Polyethylene Glycol/Nano-Hydroxyapatite Nanoparticle: Novel Fabrication and Safety Verification - Xu, Yan; Zhang, Zheng; Wang, Hehui; Zhong, Wu; Sun, Chengmei; Sun, Wei; Wu, Hongwei (Frontiers in Bioengineering and Biotechnology, 2021)
Osteosarcoma is a malignant tumor that often occurs in adolescents and children. Zoledronic acid, a new generation bisphosphonate, has been widely used as an anti-tumor drug to inhibit bone metastasis. However, the rapid renal elimination results in low effective concentration. Meanwhile, high dose intravenous zoledronic acid administration leads to severe side effects. The present study fabricated an organic-inorganic hybrid nanoparticle as the carrier of zoledronic acid. The rod-like nanoparticle, which had 150 nm length and 40 nm cross-sectional diameter, consisted of a hyaluronic acid/ polyethylene glycol (HA-PEG) polymer shell and a nano-hydroxyapatite (nHA) core, with zoledronic acid molecules loading on the surface of nHA and clearance of HA-PEG shell. The nanoparticle was characterized by microscopic analysis, in vitro release study, cytotoxicity analysis and in vivo immune response examination. Results showed that the compact and stable structure could achieve high drug loading efficiency, sustained drug release and great biocompatibility. In vitro and in vivo experiments revealed the low cytotoxicity and acceptable immune response under low-dose nanoparticle treatment, indicating its potential application for future osteosarcoma therapeutic strategies.